Residual inflammatory risk and the impact on clinical outcomes in patients after percutaneous coronary interventions. (25th October 2018) - Kalkman, Deborah N; Aquino, Melissa; Claessen, Bimmer E; Baber, Usman; Guedeney, Paul; Sorrentino, Sabato; Vogel, Birgit; de Winter, Robbert J; Sweeny, Joseph; Kovacic, Jason C; Shah, Srushti; Vijay, Pooja; et al.
Abstract: Aims: It remains unknown what percentage of patients treated with percutaneous coronary artery intervention (PCI) have high residual inflammatory risk (RIR). Moreover, the impact of RIR on clinical outcomes has not been established. The objective of this study is to determine the prevalence of patients with persistent high levels of inflammation after PCI and to evaluate clinical outcomes according to inflammatory response. Methods and results: This is a retrospective cohort study assessing patients undergoing PCI between 2009 and 2016 with serial inflammatory status assessment from a large, prospective, and single-centre PCI registry. Assessment of inflammation status with at least two high sensitive C-reactive protein (hsCRP) measurements at baseline and follow-up with >4 weeks apart. High RIR was defined as an hsCRP≥ 2 mg/L. Patients were divided into four groups: persistent high RIR, increased RIR (first low-, then high hsCRP), attenuated RIR (first high-, then low hsCRP), or persistent low RIR. The primary endpoint was all-cause mortality at 1 year follow-up. Occurrence of myocardial infarction (MI) was assessed as secondary outcome. Seven thousand and twenty-six patients were identified with serial hsCRP measurements (30.8% of all PCI patients). Of these patients 2654 (38%) had persistent high RIR, 719 patients (10%) had increased RIR, 1088 patients (15%) had attenuated RIR, and persistent low RIR was seen in 2565 patients (37%). All-cause mortality at 1 year was 2.6% in patients with persistent high RIR, compared with 1.0% in increased RIR, 0.3% in attenuated RIR, and 0.7% in persistent low RIR patients, P  < 0.01. MI at 1 year was observed in 7.5% of persistent high RIR, compared with 6.4% in increased RIR, 4.6% in attenuated RIR, and 4.3% in persistent low RIR, P  < 0.01. In an adjusted model, including accounting for diabetes mellitus, acute coronary syndrome, and baseline low-density lipoprotein, results were sustained. Conclusion: Persistent high RIR is observed frequently in patients undergoing PCI. In these patients, significantly higher all-cause mortality and MI rates are observed at 1 year follow-up. Residual inflammatory risk in patients undergoing PCI should be identified and treatment options should be further explored.